ANALISA KOEFISIEN PRODUKTIVITAS TENAGA KERJA PADA PEKERJAAN PEMBESIAN - Khubab Basari; Rendra Yoga Pradipta; Jati Utomo Dwi Hatmoko; Arif Hidayat (Jurnal Karya Teknik Sipil, 2014)
Labor’s productivity is one of the success factors in construction project. The optimal labor’s performances can be measured using the productivities coefficient of the workers. The coefficient of productivities known as BOW analysis is further updated into SNI analysis. However, the value of labor’s coefficient productivity may be different at each location depending on their performances. For example the steel work labor’s who perform their work either outside or inside the project site. Therefore, this research takes some work sites on the steel workshop and the storey building project. The purpose of this study is to know the coefficient of labor’s productivity of steel working on the workshop and the storey building project. Then, the results of the observation is compare with the benchmarks that presents at this moment, which is BOW and SNI so can be obtained the optimum coefficient values of productivity. The results revealed that the coefficient’s value of steel labor productivity for foreman in workshop, building project, BOW, SNI are 0.0179, 0.0089, 0.00 and 0.004 respectively. The value of coefficient productivity for chief worker in workshop, building project, BOW, SNI are 0.00, 0.0089, 0.255 and 0.007 respectively. In the building project, the foreman and the chief worker do not only do steel working but also doing other types of job so it assumed that both of them are doing only 60% in steel working. The value of coefficient productivity for Vulcan in workshop, building project, BOW, SNI are 0.0359, 0.0592, 0.675 and 0.07 respectively. The value of coefficient productivity for assistant worker in workshop, building project, BOW, SNI are 0.0887, 0.0726, 0.675 and 0.07 respectively. Based on the coefficient value, it can be concluded that the order value of the optimum coefficient productivity of the worker is in the  workshop, building projects, SNI and BOW.